Evaluation of Injera prepared from composite flour of Teff and Barley variety - Biadge Kefale (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2020)
Ethiopians are dependant on teff flour to make injera as staple food in Ethiopia ,although injera could be made from different cereals. The price of teff is high and the yield is low. Thus finding alternative cheaper grain and developing blend teff improved variety and barley improved variety in different ratio with acceptable and improved nutritional value would be important . this study was conducted to evaluate the nutritional value and sensory quality of injera made from a blend of teff and barley with different ratio with 10 % interval 100,90,80,70,60,50 % the nutritional value was determined using official methods and the sensory evaluation of injera was conducted at Holeta research center food science and nutrition food product development in duplicate. The result reveled that among the treatments the micro nutrients Fe and calcium were improved and the sensory quality such as taste,color and texture were good.from the study result injera quality ranked Treatment 1 up Treatment 5 could be used as an alternative option for injera utilization and provide nutritional benefit to consumers.